Digital watermarking for compressed videos - Sugiri Pranata. (2008)
In this thesis, a fast and real-time watermarking system for MPEG videos in the quantized DCT (QDCT) domain based on spread spectrum technique is designed and developed to alleviate several drawbacks suffered by other watermarking systems. A compressed-domain edge detection mechanism is incorporated to minimize the perceptual distortion of the watermarked videos. Two watermark embedding approaches, namely additive and multiplicative embedding, are investigated. While there is always a trade-off between retrieval reliability and invisibility in watermarking, our proposed system is able to achieve high watermark robustness and acceptable video fidelity.